Unveiling microbial dynamics: a review of health and immune enhancement in school settings - Asumang, Philip; Ntumi, Richard; Dwomoh, Francis (Frontiers in Microbiomes, 2024)
This review focuses on the role of microorganisms in promoting health and immune function within school environments. Microbes, including bacteria, viruses, fungi, and other microorganisms, constitute the human microbiome and play a crucial role in various bodily functions and immune system development. The complex interactions between microorganisms and the immune system in schools, where children spend a significant amount of time, are not fully understood. While schools have traditionally emphasized hygiene practices to prevent the spread of infectious diseases, recent research has highlighted the potential consequences of reduced microbial exposure during early life. The “hygiene hypothesis” suggests that limited exposure to microbes in infancy may increase the risk of allergies, asthma, and autoimmune diseases in adulthood. This paper explores the microbial diversity found in schools, the benefits of exposure to different microorganisms, and the implications of hygiene practices on immune system development. It also examines current research on microbial intervention strategies and their potential to influence overall health in schools. Understanding the role of microbes in school environments has implications for public health policies and educational practices, aiming to create healthier and more conducive learning environments for the younger generation. By comprehensively exploring this topic, this review contributes to a broader understanding of the significance of microbes in promoting health and immune function in school settings and its relevance to future health research.